Design principles for sustainability: Tearfund's expanding international development approach. Issue 2 (17th February 2022) - Simpson, Nicholas Philip; Daehnhardt, Madleina
ABSTRACT: This article introduces the role that design principles play in Tearfund's expanding approach to international development practice. Mindful that development gains can be undermined by degraded environments, Tearfund now encourages a focus on taking steps towards greater ecological integrity alongside economic and social imperatives when working with poor and vulnerable communities worldwide. We explain the purpose and goals of the "design principles" and consider how they translate principles of sustainability into practice. We discuss how the design principles extend the faith-based international NGO's work to conceptualise and operationalise holistic development more effectively, in line with the Sustainable Development Goals (SDGs). GRAPHICAL ABSTRACT: UF0001